Respuesta :

6 ≤ 5(x - 4) -2(-x + 1)

First, distribute 5 to all terms within the first parenthesis, and -2 to all terms in the second parenthesis

6 ≤ (5x - 20 + 2x -2)

Combine like terms

6 ≤ (5x + 2x - 20 - 2)

6 ≤ 7x - 22

Isolate the x. Do the opposite of PEMDAS. Note that what you do to one side you to the other.

Add 22 to both sides

6 (+22) ≤ 7x - 22 (+22)

28 ≤ 7x

Divide 7 from both sides

28/7 ≤ 7x/7

28/7 ≤ x

4 ≤ x is your answer

Use a closed dot (because of the equal underneath) on 4, and go left with an arrow

hope this helps